THE EFFECT OF CORPORATE GOVERNANCE, DIVIDEND POLICY, CONSERVATISM, AND LIQUIDITY ON THE VALUE OF FAMILY MANUFACTURING COMPANIES IN INDONESIA STOCK EXCHANGE - Wijaya, Henryanto; Cahyadi, Hadi; Salim, Susanto; Morgan, Christopher Elihu Billy (International Journal of Application on Economics and Business, 2023)
This study aims to determine whether corporate governance (which includes the board of commissioners and audit committee), dividend policy, conservatism, and liquidity affect firm value. This research will produce outputs in the form of scientific articles that are expected to be beneficial for parties who need them, such as helping internal companies to increase company value and helping investors to make decisions before investing, and being able to predict company value by looking at its financial statements, especially in related indicators. As well as useful as a reference for future researchers. Given the number and breadth of problems that must be solved, the researchers limit the issues examined in this study. It starts from the variables used, namely the dependent and independent variables. The research will be conducted for three years, from 2018 to 2020, using a family manufacturing company. It was listed on the Indonesia Stock Exchange (IDX). Researchers will use quantitative research methods, where this research is research used to examine populations and samples, using secondary data obtained from the IDX through the website www.idx.co.id and the company's website. Existing data will be entered into Microsoft Excel 2010 and processed using EViews version 11. In this study, researchers used the Non-Probability Sampling technique in taking samples, where the method does not provide equal opportunities for each population. Data collection for 2018-2020 is expected to provide the latest data.